Symbol positions‐based Slepian–Wolf coding with application to distributed video coding. Issue 11 (14th August 2020) - Benierbah, Said; Khamadja, Mohammed
Abstract : In this study, the authors will show that coding the positions of the symbols, instead of their values, can be a good way to implement efficient Slepian–Wolf (SW) coding and can reduce the complexity of both the encoder and the decoder. The authors will also propose a practical distributed video coding (DVC) system that exploits this idea. This system will use binary maps to indicate the positions of the most probable symbols, instead of separating them into bitplanes. Simulations show that this position‐based SW coding allows a simple and more efficient DVC system with improved rate‐distortion performance, compared to the bitplane‐based DVC system that uses the same side information. The memory requirements at the encoder are reduced by about 50% and the number of channel coding operations is also reduced. This DVC system also allows to use an easy way to control quantisation, reduces the decoding latency, and allows fast parallel decoding.